Main special orthopedic tests for semiological evaluation of the knee: a narrative literature review (Research, Society and Development, 2022)
Introduction: biomechanical tests were developed in medicine so that semiology and propaedeutics could begin to identify impasses related to the patellofemoral joint, these were called orthopedic knee tests, which can be associated with various pathologies that are routine in the life of the orthopedist and that save time, money and psychological distress for the patient. Objective: to present concrete data about which semiological exams are the main and most relevant in clinical practice so far for the orthopedic evaluation of the knee. Methodology: this is a narrative literature review. The research was carried out through online access to the Google Scholar, Virtual Health Library (BVS) and EBSCO Information Services databases. Results and discussion: the literature was controversial in indicating a "gold standard test for the physical examination of the knee" for the diagnosis of meniscus and ligament injuries that affect this joint, this is related to the difficulty in standardizing the tests performed, which results in indices of broad accuracy. As an example of this, we have the divergences between studies that consider only clicks as a positive result in the McMurray test, while other authors establish that there is a need for a click and pain report by the patient for the test to be, in fact, positive. In general, the authors agree that physical examination maneuvers, despite being an excellent method for the initial assessment of the patient, do not present great diagnostic value, demanding other elements for a more accurate and reliable diagnosis that allows surgical interventions, such as imaging exams. Conclusion: good technique must consider each part being evaluated and also the sensitivity of the test. It is extremely important that you assess the opposite knee to obtain a parameter for the patient being examined. Although the imaging tests are quite complete and detailed, the physical examination of the knee is the most reliable for obtaining a more accurate diagnosis.